(untitled) (Libya Journal of Geographical Studies, 2023)
The brain drain from Palestine is a dangerous phenomenon that threatens Palestinian society, especially during the aggravation of this phenomenon in the absence of political and economic stability and the persistence of Israeli violations and crimes against the Palestinians. This study aims to identify the reality of brain drain in Palestine and to try to identify the most important causes leading to this phenomenon and its consequences. The researchers used the descriptive analytical approach as one of the appropriate approaches for such studies. In addition, several methods have been used, such as in-depth interviews, charts, questionnaires...etc. The study reached several results, including: The division and the political conflict between Gaza and the West Bank are a major cause of the exacerbation of the phenomenon of brain drain and Palestinian youth. The study concluded with many results, including the call for a comprehensive strategy for human development in Palestine to provide an appropriate and nurturing environment for Palestinian competencies to ensure the correct investment of Palestinian.